Management of the Imarah of the At-Taqwa Mosque in Increasing Religious Knowledge of the Kutacane Congregation - Musliadi Musliadi; Tengku Walisyah (Universitas KH. Abdul Chalim Mojokerto, 2024)
The characteristic that is visible now is that the mosque functions only as a place for prostration and not for other worship activities. Management efforts to improve the welfare of mosques can be carried out by increasing religious activities by implementing systematic and organized mosque management, awareness, and activities over a longer period. The urgency of this research is that many mosque managers in the current era do not have leadership skills and abilities. On that basis, researchers want to see how the management of the at-Taqwa Kutacane mosque is managed, where the mosque is under the auspices of the government. This research is field research located at the at-Taqwa Kutacane mosque. Collecting data and information through interviews, observation, and documentation. The data analysis technique used in this research is the Milles and Huberman qualitative model. The results of this research found that the implementation of the management of the at-Taqwa mosque has been carried out well. One of the managements carried out by the mosque imamate to increase the congregation's religious knowledge is by creating 4 programs, namely: Planning, organizing, implementing, and supervising programs. The management of the imamate of the at-Taqwa mosque is very good because the efforts made by the imamate management to increase religious knowledge are very rarely found in other mosques. On that basis, this management is very appropriate to be implemented in other mosques to provide comfort for the congregation.